Work-related stressors and coping behaviors among leaders in small and medium-sized IT and technological services enterprises - Dannheim, Indra; Buyken, Anette; Kroke, Anja (BMC Public Health)
Abstract Background Occupational health interventions for leaders are underrepresented in small and medium-sized enterprises (SMEs). When creating and developing effective occupational health interventions, identification of the specific needs of the target group is regarded as an essential step before planning an intervention. Therefore, the aim of this study was (1) to examine the subjectively experienced work-related stressors of leaders in small and medium-sized IT and technological services enterprises, (2) to explore coping behaviors leaders use to deal with the experienced work-related stressors, (3) to investigate resources supporting the coping process and (4) to identify potentially self-perceived consequences resulting from the experienced stressors. Methods Ten semi-structured interviews with leaders in small and medium-sized IT and technological services enterprises were conducted. The interviews were transcribed and analyzed with content-structuring qualitative content analysis in accordance to Kuckartz. Results Leaders in small and medium-sized IT and technological services enterprises experience various stressors caused by work organization as well as industry-related stressors and other work-related stressors. To address the experienced stressors, leaders apply problem focused coping behaviors (e.g. performing changes on structural and personal level), emotional focused coping behaviors (e.g. balancing activities, cognitive restructuring) as well as the utilization of social support. Helpful resources for the coping process include organizational, social and personal resources. As a result of the experienced work-related stressors, interviewees stated to experience different health impairments, negative effects on work quality as well as neglect of leisure activities and lack of time for family and friends. Conclusion The identified experienced work-related stressors, applied coping behaviors, utilized resources and emerging consequences underpin the urgent need for the development and performance of health-oriented leadership interventions for leaders in small and medium- sized IT and technological services. The results of this study can be used when designing a target-oriented intervention for the examined target group.
Keywords: Public Health; Environmental and Occupational Health

Choice architecture interventions promoting sustained healthier food choice and consumption by students in a secondary school setting: A systematic review of intervention studies - Schulte, Eva A.; Winkler, Gertrud; Brombach, Christine; Buyken, Anette (Public Health Nutrition)
Abstract Objective: To systematically review the impact of choice architecture interventions (CAI) on the food choice of healthy adolescents in a secondary school setting. Factors potentially contributing to the effectiveness of CAI types and numbers implemented and its long-term success were examined. Design: PUBMED and Web of Science were systematically searched in October 2021. Publications were included following predefined inclusion criteria and grouped according to number and duration of implemented interventions. Intervention impact was determined by systematic description of the reported quantitative changes in food choice and/or consumption. Intervention types were compared with regards to food selection and sustained effects either during or following the intervention. Setting: CAI on food choice of healthy adolescents in secondary schools. Participants: Not applicable Results: Fourteen studies were included; four randomized controlled trials and five each of controlled or uncontrolled pre-post design, respectively. Four studies implemented a single CAI type, with ten implementing > 1. Three studies investigated CAI effects over the course of a school year either by continuous or repeated data collection, while ten studies’ schools were visited on selected days during intervention. Twelve studies reported desired changes in overall food selection, yet effects were not always significant, and appeared less conclusive for longer term studies. Conclusions: This review found promising evidence that CAI can be effective in encouraging favorable food choices in healthy adolescents in a secondary school setting. However, further studies designed to evaluate complex interventions are needed.
Keywords: Public Health; Environmental and Occupational Health; Nutrition and Dietetics; Medicine (miscellaneous)

Effect of a controlled lifestyle intervention on medication use and costs: The Healthy Lifestyle Community Program (cohort 2) - Kranz, Ragna-Marie; Kettler, Carmen; Anand, Corinna; Koeder, Christian; Husain, Sarah; Schoch, Nora; Buyken, Anette; Englert, Heike (Nutrition and Health)
Background: Establishing a healthy lifestyle has a great potential to reduce the prevalence of non-communicable diseases (NCDs) and their risk factors. NCDs contribute immensely to the economic costs of the health care system arising from therapy, medication use, and productivity loss. Aim: The aim of this study was to evaluate the effect of the Healthy Lifestyle Community Program (cohort 2; HLCP-2) on medication use and consequently on medication costs for selected NCDs (diabetes, hypertension, and dyslipidemia). Methods: Data stem from a 24-month non-randomised, controlled intervention trial aiming to improve risk factors for NCDs. Participants completed questionnaires at six measurement time points assessing medication use, from which costs were calculated. The following medication groups were included in the analysis as NCD medication: glucose-lowering medications (GLM), antihypertensive drugs (AHD) and lipid-lowering drugs (LLD). Statistical tests for inter- and intra-group comparison and multiple regression analysis were performed. Results: In total, 118 participants (intervention group [IG]: n = 79; control group [CG]: n = 39) were considered. Compared to baseline medication use decreased slightly in the IG and increased in the CG. Costs for NCD medication were significantly lower in the IG than in the CG after 6 ( p = 0.004), 12 ( p = 0.040), 18 ( p = 0.003) and 24 months ( p = 0.008). After multiple regression analysis and adjusting for confounders, change of costs differed significantly between the groups in all final models. Conclusion: The HLCP-2 was able to moderately prevent an increase of medication use and thus reduce costs for medication to treat NCDs with the greatest impact on AHD. Trial registration German Clinical Trials Register DRKS ( www.drks.de ; reference: DRKS00018775).
Keywords: Nutrition and Dietetics; General Medicine; Medicine (miscellaneous)

Full Breastfeeding and Allergic Diseases—Long-Term Protection or Rebound Effects? - Libuda, Lars; Filipiak-Pittroff, Birgit; Standl, Marie; Schikowski, Tamara; von Berg, Andrea; Koletzko, Sibylle; Bauer, Carl-Peter; Heinrich, Joachim; Berdel, Dietrich; Gappa, Monika (Nutrients)
A previous follow-up of the GINIplus study showed that breastfeeding could protect against early eczema. However, effects diminished in adolescence, possibly indicating a “rebound effect” in breastfed children after initial protection. We evaluated the role of early eczema until three years of age on allergies until young adulthood and assessed whether early eczema modifies the association between breastfeeding and allergies. Data from GINIplus until 20-years of age (N = 4058) were considered. Information on atopic eczema, asthma, and rhinitis was based on reported physician’s diagnoses. Adjusted Odds Ratios (aOR) were modelled by using generalized estimating equations. Early eczema was associated with eczema (aORs = 3.2–14.4), asthma (aORs = 2.2–2.7), and rhinitis (aORs = 1.2–2.7) until young adulthood. For eczema, this association decreased with age (p-for-interaction = 0.002–0.006). Longitudinal models did not show associations between breastfeeding and the respective allergies from 5 to 20 years of age. Moreover, early eczema generally did not modify the association between milk feeding and allergies except for rhinitis in participants without family history of atopy. Early eczema strongly predicts allergies until young adulthood. While preventive effects of full breastfeeding on eczema in infants with family history of atopy does not persist until young adulthood, the hypothesis of a rebound effect after initial protection cannot be confirmed.
Keywords: Food Science; Nutrition and Dietetics

Ernährungsarmut unter Pandemiebedingungen - Birner, Regina; Linseisen, Jakob; Arens-Azevedo, Ulrike; Balmann, Alfons; Biesalski, Hans Konrad; Bosy-Westphal, Anja; Buyken, Anette; Döring, Thomas; Feindt, Peter; Götz, Kay-Uwe; Iweala, Sarah; Martínez, José; et al. (Berichte über Landwirtschaft)
Ernährungsarmut wird als Problem in Deutschland weitgehend vernachlässigt. Von materieller Ernährungsarmut betroffen sind Menschen, denen es aufgrund fehlender finanzieller Mittel nicht möglich ist, sich gesundheitsfördernd zu ernähren. Etwa 3,5 % der Bevölkerung (rund drei Millionen Menschen) sind durch materielle Ernährungsarmut gefährdet. Damit einher geht oft auch soziale Ernährungsarmut, die Menschen von der sozialen Teilhabe ausschließt, die z. B. durch gemeinsames Essen ermöglicht wird. Essen ist nicht nur von Bedeutung für die körperliche Gesundheit, sondern auch zentral für die psychische Gesundheit und das Wohlbefinden sowie für die soziale Zugehörigkeit, was sich wiederum auf die körperliche Gesundheit auswirkt. Die sozialen Funktionen des Essens werden vielfach übersehen – und bei der Berechnung des Regelbedarfs ausgeblendet. Gerade die Corona-Pandemie hat gezeigt, wie fehlende soziale Kontakte und sozialer Ausschluss sich auf die physische, psychische und soziale Gesundheit auswirken können. Aus Sicht des WBAE (Wissenschaftliche Beirat für Agrarpolitik, Ernährung und gesundheitlichen Verbraucherschutz) ist deshalb der integrative Blick auf die materielle und soziale Ernährungsarmut zentral, da sie sich gegenseitig verstärken können. Diese Stellungnahme befasst sich mit der Frage, wie sich die Corona-Pandemie auf von Ernährungsarmut gefährdete Menschen ausgewirkt hat und was daraus gelernt werden kann. Ein wichtiger Aspekt ist der zeitweilige Wegfall von Essensangeboten in Kitas, Schulen, Tafeln und anderen karitativen Essensangeboten, die ein Sicherheitsnetz für Menschen in Ernährungsarmut darstellen. Die Stellungnahme zieht auf dieser Basis auch Schluss-folgerungen zur Ernährungsarmut außerhalb von Pandemiebedingungen. Im Hinblick auf die Notwendigkeit der Vermeidung von Fehlernährung in Haushalten, die von Ernährungsarmut bedroht sind, kommt der WBAE zu dem Schluss, dass diese Risikogruppe während der Pandemie nicht ausreichend im Fokus der Maßnahmen zur Abmilderung der Pandemiefolgen stand. Dies zeigt sich schon daran, dass kaum Daten erhoben wurden. Deutschland verfügt über kein klares Indikatoren- und Zielsystem und kein Monitoring zur Ernährungsarmut. Die wenigen vorhandenen Daten weisen auf problematische Entwicklungen hin. Insgesamt wurden durch den Bund sehr umfangreiche Mittel zur Bewältigung der wirtschaftlichen und sozialen Folgen der Corona-Pandemie und zur Einkommenssicherung während der Pandemie eingesetzt. Dies ist unter dem Blickwinkel „Ernährungsarmut” positiv zu bewerten. Es ist davon auszugehen, dass diese Maßnahmen verhindert haben, dass noch mehr Haushalte von Ernährungsarmut betroffen waren. Insgesamt zeigt die Analyse jedoch, dass es kaum gezielte Maßnahmen gab, um den Ausfall von Kita- und Schulernährung durch alternative Formen der Bereitstellung von Lebensmitteln oder einer warmen Mahlzeit aufzufangen. Maßnahmen auf Bundesebene fehlten, um Länder, Kommunen und nicht-staatliche Organisationen dabei zu unterstützen. Auswertungen der Pandemiemaßnahmen vergleichbarer Länder zeigen, dass dort schnelle und flexible Maßnahmen zur Bereitstellung von Lebensmitteln eine wichtige Rolle gespielt haben, um armutsgefährdete Haushalte zu unterstützen. In Deutschland wurden vorwiegend finanzielle Transfers genutzt, z. T. zeitlich verzögert und wenig zielgruppenspezifisch. Vor diesem Hintergrund hat der WBAE mögliche Maßnahmen gegen Ernährungsarmut – in Krisen, aber auch generell – untersucht: (1) finanzielle Transfers (einmalig oder fortlaufend), (2) Lebensmittelgutscheine („Voucher“), (3) Lebensmittelpakete und (4) warme Mahlzeiten, wobei die letzten beiden Optionen jeweils zur Abholung oder zur Auslieferung angeboten werden können. Die untersuchten internationalen Beispiele zeigen Möglichkeiten, wie z. T. mit schnellen und teilweise innovativen Ansätzen auf Lockdown-Maßnahmen reagiert wurde. Im Grundsatz spricht aus Sicht des WBAE aber vieles für das deutsche System zur Bekämpfung der Ernährungsarmut, das im Kern auf einem Bürgergeld beruht. Ein solches Bürgergeld muss jedoch ausreichend sein, um materielle und soziale Ernährungsarmut zu vermeiden. Die aktuellen, im Bürgergeld für Essen und Getränke zur Verfügung stehenden Beträge entsprechen allerdings nicht diesem Anspruch. Bei der Einführung des Bürgergelds im Jahr 2023 wurde zwar zeitnah auf die hohe Inflation reagiert. Die Berechnungsmethodik für die Bedarfsermittlung wurde aber nicht angepasst, sodass der Regelsatz nach wie vor nicht für eine gesundheitsfördernde Ernährung ausreicht. Die soziale Funktion von Ernährung wird bei der Berechnung des Regelsatzes nicht berücksichtigt. Um bei akutem Handlungsbedarf, wie z. B. auch bei der derzeitigen Inflation, schneller reagieren zu können, sollten außerdem Systeme zur Auszahlung sozial differenzierter „Krisentransfers” an vulnerable Haushalte mit geringem Verwaltungsaufwand ermöglicht werden. Darüber hinaus sollte für den zentralen Bereich der Kinder-ernährung der Schutz einer adäquaten Grundsicherung durch einen Systemwechsel zu einer integrativen, beitragsfreien und somit nicht-diskriminierenden Kita- und Schulverpflegung ergänzt werden, die zudem den DGE-Qualitätsstandards entspricht. Schließlich sollte der Staat privates, ehrenamtliches Engagement ergänzend fördern, z. B. durch Infrastrukturunterstützung bei karitativen Essensangeboten. Eine Herausforderung der Gestaltung von karitativen Lebensmittelangeboten besteht darin, dass sie oft als stigmatisierend und beschämend wahrgenommen werden und der Nachweis eines Anspruches teils schwierig ist. Zudem bestehen oft nur wenige Wahlmöglichkeiten, sodass individuelle Präferenzen oder Unverträglichkeiten nur sehr eingeschränkt berücksichtigt werden können. Im Hinblick auf die soziale Dimension der Ernährung kommt hinzu, dass wichtige soziale Funktionen des Essens, wie das gemeinsame Essen, also Kommensalität, nicht oder nur sehr eingeschränkt ermöglicht wird. Auch bleiben diejenigen, die versorgt werden, dabei meist unter sich. Vor dem Hintergrund dieser Gesamteinschätzung empfiehlt der WBAE die folgenden, in Abbildung Z 1 dargestellten Maßnahmen (siehe Beitrag). Zusammenfassend betont der WBAE die in Deutschland weiterhin unterschätzten Risiken materieller und sozialer Ernährungsarmut. Im Rahmen der geplanten Nationalen Ernährungsstrategie der Bundesregierung sollte dem Thema Ernährungsarmut aus Sicht des WBAE eine herausgehobene Bedeutung zugemessen werden.

Perspective: A Conceptual Framework for Adaptive Personalized Nutrition Advice Systems - Renner, Britta; Buyken, Anette; Gedrich, Kurt; Lorkowski, Stefan; Watzl, Bernhard; Linseisen, Jakob; Daniel, Hannelore; Conrad, Johanna; Ferrario, Paola G.; Holzapfel, Christina; Leitzmann, Michael; Richter, Margrit; et al. (Advances in Nutrition)
Keywords: Nutrition and Dietetics; Medicine (miscellaneous); Food Science

Dietary protein intake and health-related outcomes: a methodological protocol for the evidence evaluation and the outline of an evidence to decision framework underlying the evidence-based guideline of the German Nutrition Society - Kroke, Anja; Schmidt, Annemarie; Amini, Anna M.; Kalotai, Nicole; Lehmann, Andreas; Haardt, Julia; Bauer, Jürgen M.; Bischoff-Ferrari, Heike A.; Boeing, Heiner; Egert, Sarah; Ellinger, Sabine; Kühn, Tilman; et al. (European Journal of Nutrition)
Abstract Purpose The present work aimed to delineate (i) a revised protocol according to recent methodological developments in evidence generation, to (ii) describe its interpretation, the assessment of the overall certainty of evidence and to (iii) outline an Evidence to Decision framework for deriving an evidence-based guideline on quantitative and qualitative aspects of dietary protein intake. Methods A methodological protocol to systematically investigate the association between dietary protein intake and several health outcomes and for deriving dietary protein intake recommendations for the primary prevention of various non-communicable diseases in the general adult population was developed. Results The developed methodological protocol relies on umbrella reviews including systematic reviews with or without meta-analyses. Systematic literature searches in three databases will be performed for each health-related outcome. The methodological quality of all selected systematic reviews will be evaluated using a modified version of AMSTAR 2, and the outcome-specific certainty of evidence for systematic reviews with or without meta-analysis will be assessed with NutriGrade. The general outline of the Evidence to Decision framework foresees that recommendations in the derived guideline will be given based on the overall certainty of evidence as well as on additional criteria such as sustainability. Conclusion The methodological protocol permits a systematic evaluation of published systematic reviews on dietary protein intake and its association with selected health-related outcomes. An Evidence to Decision framework will be the basis for the overall conclusions and the resulting recommendations for dietary protein intake.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Sixteen-week multicentre randomised controlled trial to study the effect of the consumption of an oat beta-glucan-enriched bread versus a whole-grain wheat bread on glycaemic control among persons with pre-diabetes: a study protocol of the CarbHealth study - Hjorth, Therese; Schadow, Alena; Revheim, Ingrid; Spielau, Ulrike; Thomassen, Lise M; Meyer, Klara; Piotrowski, Katja; Rosendahl-Riise, Hanne; Rieder, Anne; Varela, Paula; Lysne, Vegard; Ballance, Simon; et al. (BMJ Open)
Introduction In 2012, the estimated global prevalence of pre-diabetes was 280 million, and the prevalence is expected to rise to 400 million by 2030. Oat-based foods are a good source of beta-glucans, which have been shown to lower postprandial blood glucose. Studies to evaluate the effectiveness of the long-term intake of beta-glucan-enriched bread as part of a habitual diet among individuals with pre-diabetes are needed. Therefore, we designed a multicentre intervention study in adults with pre-diabetes to investigate the effects of consumption of an oat-derived beta-glucan-enriched bread as part of a normal diet on glycated haemoglobin (HbA1c) in comparison to consumption of whole-grain wheat bread. Methods and analysis The CarbHealth trial is a multicentre double-blind randomised controlled 16-week dietary intervention trial in participants 40–70 years of age with a body mass index of ≥27 kg/m 2 and HbA1c of 35–50 mmol/mol. The study is conducted at four universities located in Norway, Sweden and Germany and uses intervention breads specifically designed for the trial by Nofima AS. The aim is to recruit 250 participants. The primary outcome is the difference in HbA1c between the intervention and the control groups. The main analysis will include intervention group, study centre and baseline HbA1c as independent variables in an analysis of covariance model. Ethics and dissemination The study protocol was approved by respective ethical authorities in participating countries. The results of the study will be communicated through publication in international scientific journals and presentations at (inter)national conferences. Trial registration number NCT04994327 .
Keywords: General Medicine

Correction: Short-term effects of carbohydrates differing in glycemic index (GI) consumed at lunch on children's cognitive function in a randomized crossover study. - Jansen, K; Tempes, J; Drozdowska, A; Gutmann, M; Falkenstein, M; Buyken, Anette; Libuda, Lars; Rudolf, H; Lücke, T; Kersting, M (Eur J Clin Nutr)

Health relevance of lowering postprandial glycaemia in the paediatric population through diet': results from a multistakeholder workshop. - Vinoy, S; Goletzke, J; Rakhshandehroo, M; Schweitzer, L; Flourakis, M; Körner, A; Alexy, U; van Schothorst, EM; Ceriello, A; Zakrzewski-Fruer, JK; Buyken, Anette (Eur J Nutr)

Zur Erinnerung: Warum Bildung für Lebensführung immer eine politische Dimension hat. Das Beispiel Nationalsozialismus - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Konzepte von Qualität in ihrer Bedeutung für Konsumentscheidungen verstehen - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung von Ressourcen für die Lebensgestaltung verstehen - Schlegel-Matthies, Kirsten; Methfessel, Barbara (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten; Bartsch, Silke; Brandl, Werner; Methfessel, Barbara

Die Bedeutung von Ressourcen für Lebensqualität und gesellschaftliche Teilhabe - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Lebensführung und Umgang mit Diversität– Haushaltswissenschaftliche Perspektiven - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Die Organisation der Daseinsvorsorge für die private Lebensführung reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Lehren gestalten – Lernen ermöglichen. Fachdidaktische Hinweise - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Lebensweise, Lebensführung und Lebensstile reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Ernährungs- und Verbraucherbildung zwischen Wissenschaft und Lebenswelt - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)